Obama’s Afghanistan strategy: a policy of balancing the reality with the practice - Ra'ees, Wahabuddin (2012)
President Barak H. Obama promised that his administration in pursuit of the US interests would stabilize Afghanistan. President Obama in 2009 introduced the AfPak or Afghanistan and Pakistan Policy. Obama’s AfPak Policy in outlining America’s intentions in Afghanistan was announced over two phases: the Obama March 27, 2009, Afghanistan Strategy and the Obama December 1, 2009, Afghanistan Strategy. The US AfPak Policy’s recognition that there is no military-only solution to the Afghan quagmire and focus on soft powers and nation building efforts distinguishes it from Bush’s Afghanistan Policy. The Obama AfPak Policy will terribly fail if the US abandons the intra-Afghan dialogue and if the dialogue it suggests with powers with stakes results in ‘sourcing out’ Afghanistan again. President Obama should not have made public the July 2011 deadline for a drawdown and eventual withdrawal of US troops from Afghanistan in his December 1, 2009, tier of AfPak Policy announcement. Disengagement or abandoning Afghanistan entails serious consequences for the US interests in the region. The US has a ‘stabilizing’ role and therefore must work out an alternative approach such as strengthening the existing ‘declaration of strategic partnership’ with Afghanistan to remain engaged. Sending additional troops jeopardizes the US chances of not seen as occupying force by the Afghans similar to the Soviet Union. The Obama administration should have shared Secretary Gates’s fear that the Afghans will view the US as an occupying power similar to the Soviet Union when deliberating on sending additional troops requested by the US Commander in Afghanistan, General Stanley McChrystal.